The synergy of creativity and critical thinking in engineering design: The role of interdisciplinary augmentation and the fine arts. (May 2016) - Spuzic, S.; Narayanan, R.; Abhary, K.; Adriansen, H.K.; Pignata, S.; Uzunovic, F.; Guang, Xu
Abstract: Analysis of the impact of interaction and experience on quality components such as "usability", "producibility", "reliability", "sustainability" and "aesthetics" is presented using the case of engineering design, a discipline that traditionally has an image of being a strictly calculated, rigid framework. It has been widely recognised that engineering design encompasses two ways of thinking—creative and critical. A central argument that the synergy of creativity and criticality is significantly enhanced by connecting true interdisciplinary augmentation with the fine arts is discussed along with reflecting on the importance of such an approach in higher education. Highlights: Analysis of the impact of interactions and experiences on quality components of engineering design is presented. The concepts such as producibility, reliability, sustainability and aesthetics are analysed. The synergy of creativity and criticality is significantly enhanced by releasing true interdisciplinary augmentation with fine art.